الأصوات العربية عند الخليل في ضوء علم الأصوات الحديث - holimi, muhammad; Abdurrohman, Wahid; Shobirin, Shobirin (Lugawiyyat, 2024)
This study aims to explore and analyze the Arabic sounds established by Al-Khalil in his Al-Ain dictionary in the light of modern phonology. This study used the descriptive analytical method through a desk study to reach the research results. This study concluded that Al-Khalil set the limits of phonetic study through his book Al-Ain, in which he specified the exits of sounds and some of their characteristics to distinguish between sounds that are united in output and similar in many characteristics. He also applied a scientific approach in his audio studies that was similar in many aspects to the approach followed by the hadith scholars, according to simple capabilities made available to him by the time period in which he lived.